2022
DOI: 10.3389/fendo.2022.969914
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the key ligand receptor CADM1_CADM1 in the regulation of thyroid cancer based on scRNA-seq and bulk RNA-seq data

Abstract: IntroductionAdvanced papillary thyroid cancer (PTC) has a poor prognosis, 60~70% of which become radio iodine refractory (RAI-R), but the molecular markers that assess PTC progress to advanced PTC remain unclear. Meanwhile, current targeted therapies are badly effective due to drug resistance and adverse side effects. Ligand-receptor pairs (L/R pairs) play an important role in the interactions between tumor cells and other cells in the tumor microenvironment (TME). Nowadays, therapies targeting ligand-receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Detailed analysis of scRNA-seq data from thyroid cancer cells has aided in the identification of novel biomarkers for PTC. Specifically, it has pointed out a critical LR pair biomarker, cell adhesion molecule 1 (CADM1)-CADM1, associated with a favourable prognosis in PTC [29]. Interestingly, the expression of CADM1-CADM1 was downregulated in PTC, and overexpression of CADM1 could inhibit tumour cell invasion and migration [29].…”
Section: Novel Biomarkers For Therapeutic Discoverymentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed analysis of scRNA-seq data from thyroid cancer cells has aided in the identification of novel biomarkers for PTC. Specifically, it has pointed out a critical LR pair biomarker, cell adhesion molecule 1 (CADM1)-CADM1, associated with a favourable prognosis in PTC [29]. Interestingly, the expression of CADM1-CADM1 was downregulated in PTC, and overexpression of CADM1 could inhibit tumour cell invasion and migration [29].…”
Section: Novel Biomarkers For Therapeutic Discoverymentioning
confidence: 99%
“…Specifically, it has pointed out a critical LR pair biomarker, cell adhesion molecule 1 (CADM1)-CADM1, associated with a favourable prognosis in PTC [29]. Interestingly, the expression of CADM1-CADM1 was downregulated in PTC, and overexpression of CADM1 could inhibit tumour cell invasion and migration [29]. CADM1-CADM1 was more highly expressed in younger populations under 50 years old and stage I, compared to stage II and older populations over 50 years old [29].…”
Section: Novel Biomarkers For Therapeutic Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study confirmed that radixin (RDX), the gene with the highest hazard ratio (HR) among the PANoptosis prognosis‐related genes, was prominently expressed in arterial endothelial cells (ECs). This investigation enriches our comprehension of the involvement of PANoptosis in breast cancer and offers promising new directions for breast cancer immunotherapy 135 …”
Section: Panoptosis In Cancermentioning
confidence: 76%
“…This investigation enriches our comprehension of the involvement of PANoptosis in breast cancer and offers promising new directions for breast cancer immunotherapy. 135…”
Section: Breast Cancermentioning
confidence: 99%